Plant-Derived Triterpenoid Functionalization: Synthesis of α-Acyloxycarboxamides - Fidel Rodriguez-Lopez; Edgar G. Rodríguez-García; Hugo A. García-Gutiérrez; Rocío Gámez-Montaño (Chemistry Proceedings, 2023)
The application of isocyanide-based multicomponent reactions (IMCRs) for triterpenoid functionalization has been little reported. Triterpenoids and their derivatives are an important class of natural products of interest in medicinal chemistry due to their potential applications as antibacterial, antifungal, and cytotoxic agents. Herein, we describe the use of ethanol as a solvent in the Passerini reaction for the functionalization of masticadienonic acid isolated from fruits and peduncles of P. mexicana. A small series of α-acyloxycarboxamides was synthesized with moderate to good overall yields of 33 to 57%, evaluating and extending the scope of the aldehyde component.